THE EFFECTIVENESS OF DEMODICOSIS MANAGEMENT IN PEKING DOGS USING A COMBINATION OF IVERMECTIN AND AMITRAZ - Kumara, I Dewa Made Upadana; Arjentinia, I Putu Gede Yudhi; Widyastuti, Sri Kayati (Buletin Veteriner Udayana, 2025)
Demodicosis is a skin disease caused by Demodex mites and is commonly found in dogs. This study aims to evaluate the effectiveness of a combination of ivermectin and amitraz for the treatment of demodicosis in dogs. A three-year-old male Pekingese dog weighing 5.5 kg was presented to the Internal Medicine Laboratory, Faculty of Veterinary Medicine, Udayana University, exhibiting lethargy and hair loss in the back, neck, legs, and extremities. Physical examination revealed alopecia, erythema, skin thickening, oily and scaly skin, a rancid odor, and hyperpigmentation. The dog exhibited a high level of pruritus. Routine hematological examination showed the dog was experiencing anemia and leukocytopenia. The diagnosis was confirmed as demodicosis based on microscopic examination of deep skin scrapings. The prognosis for this case was considered favorable. The dog was treated with subcutaneous ivermectin (Wormectin 0.5 mg/kg BW, PT. Medion Farma Jaya, Bandung, Indonesia) and antihistamine diphenhydramine HCL (Recodryl® 4 mg/kg BW, PT. Global Multi Pharmalab, Semarang, Indonesia). Weekly baths with amitraz (V-Traz Amitraz 12.5%, PT. Olego Mandiri Indonesia, DKI Jakarta, Indonesia) at a concentration of 500 ppm were administered, along with daily oral administration of a skin and coat supplement (Coatex® vetplus, Mega Utama Medica, DKI Jakarta, Indonesia) at a dose of one capsule. After 14 days, the dog’s condition showed improvement, with reduced scratching intensity, decreased erythema, and resolution of the previously oily skin. Supportive therapy was continued for one month, with further evaluation planned. The dog demonstrated significant recovery following the treatment, and intensive care is recommended to prevent reinfection.